The study on the requirements and child adoption process in Malaysia - Khairuddin, Irni Eliana; Ahmad Uzir, Nora’ Ayu; Ahmad Kassim, Norliya (2012)
Child adoption in Malaysia is under responsibility of National Registration Department of Malaysia and Malaysian Social Welfare department. The main objectives of this research are to identify the requirements of child adoption process of child adoption in Malaysia and to develop the process model of child adoption process in Malaysia. In general there are two types of adoptions in Malaysia - adoption of a Muslim child and adoption of a non-Muslim child (Crown, 2011). Prospective adoptive parent(s) who are non-Muslim may not adopt Muslim children. Whether it is a Muslim adoption or non-Muslim adoption, the adoptive parent(s) must be an ordinary resident in Malaysia, who are working and living in Malaysia for at least two years before the application and the prospective parent(s) may also be required to remain in Malaysia during the process, which can take some time. The Registration of Adoptions Act 1952 and relevant Syariah laws govern the adoption of a Muslim child in Malaysia. A prospective child may be identified for adoption privately or through the Social Welfare Department. A court petition is not required. The Muslim prospective adoptive parent applies to the National Registration Department to document the child as his/her adopted child. To qualify, the adoptive parent must have resided with and had continuous custody of the child for a period of not less than two years. The application should include evidence relating to the care, maintenance and education of the child during the two years from the date of the biological parent's statutory declaration relinquishing all parental rights. In Malaysia there two ways to adopt a child. It is either through direct adoption or through the Malaysian Social Welfare Program called 'Anak Pelihara'. Direct child adoption is a situation where a given child is given directly to the foster family by the biological parents. It is either the child is given since the baby were born or under 18 years old. Once the child is given to the foster family, a letter of consent needs to be made by the biological parents to declare that they are willing to give their children to the foster parents. Informal agreements between the biological and foster parents are illegal and not allowed. Together with the letter the child will be given to the foster parents. Within two years period of time, the foster parents will be monitor by the social welfare department of Malaysia. After the two years of period, the foster parents may register the adoption through a process named de facto adoption. While adoption through Malaysian Social Welfare Department is where married couple or single parent who wanted to have a child can also apply through Malaysia Social Department. There is a special program under Malaysia Social Department called "Anak Pelihara", where a child from Malaysia Social Department will be given to the future foster parents for them to take care. The whole process of adoption will be fully handled by Malaysia Social Department. The main objective of this program is to give a chance for both a married couple to have a child in the family. Both ways of adoption are currently legally practise in Malaysia.